(untitled) (International Journal of Maternal, Perinatal and Neonatal Care, 2026)
Respiratory distress remains a leading cause of admission and mortality among children under five years of age in low- and middle-income regions. In acute pediatric emergency care, the clinical competency, foundational knowledge, and rapid decision-making skills of staff nurses are critical factors determining patient survival and clinical outcomes. This mixed-methods study evaluates these professional dimensions among pediatric and emergency care nurses working in selected tertiary, secondary, and primary healthcare institutions across Uttar Pradesh. The study outlines systematic triage pathways, standardized behavioral and clinical screening scales, and evidence-based respiratory care algorithms. Quantitative evaluations reveal varying levels of clinical proficiency, with significant variations linked to institutional infrastructure, regular pediatric life support training, and professional experience. Qualitative findings identify structural barriers such as lack of specialized diagnostic devices, heavy workloads, and a lack of standardized pediatric triage protocols. This article presents targeted emergency nursing frameworks, interactive simulation training paradigms, and policy recommendations designed to improve early recognition and management of acute pediatric respiratory crises throughout the region.